ANALISIS KUALITAS PELAYANAAN TERHADAP KEPUASAN PASIEN (STUDI KASUS DI PUSKESMAS INBATE KECAMATAN BIKOMI NILULAT KABUPATEN TIMOR TENGAH UTARA) - Thein, Imelda (Aksara Public, 2019)
This study aims to determine the effect of Physical Evidence, Reliability and Responsiveness on Patient Satisfaction in Inbate Health Center, Bikomi Nilulat District, North Central Timor Regency. The data used in this study are: Primary data obtained through questionnaires distributed to 60 respondents. Analysis Method The data used are analysis of validity and reliability, classic assumption test and multiple linear regression using SPSS 21 program. The results showed that based on partial test (t test), Physical Evidence does not affect Patient Satisfaction in Inbate Health Center, Bikomi Nilulat District, Timor Regency North Central with a significance of 0.373> 0.05. Whereas Reliability and Responsiveness have an effect on Patient Satisfaction in Inbate Community Health Center, Bikomi Nilulat District, North Central Timor Regency with significance of 0.004 and 0.009 <0.05. Simultaneously (F test), Physical Evidence, Reliability and Responsiveness have an effect on Patient Satisfaction in Inbate Health Center, Bikomi Nilulat District, Timor Tengah Utara Regency with significance of 0,000 <0,05.